Improving the visibility of bicycle infrastructure. - Fabriek, Eva; Waard, Dick de; Schepers, Paul J. (Inderscience Enterprises, 2012)
The visual characteristics of road infrastructure play a major role in a substantial number of single-bicycle crashes. The focus of this research was on finding the most common situations that result in a poorly visible bicycle infrastructure, and investigating how to improve these conditions for vulnerable cyclist populations, specifically the visually impaired and the older cyclist. Three studies were performed, a questionnaire study amongst visually impaired cyclists, focus group discussions with older cyclists, and an experiment on a closed track where participants' vision, in particular their contrast sensitivity, was impaired. The results from the questionnaire study and the focus group discussions revealed that bollards, kerbs, and cycle path markings/shoulders are the most critical visual elements in the road infrastructure. In addition, cycling performance and cyclists' feelings of safety worsened in conditions where the visibility of obstacles and the road's course were the poorest. Visibility can be enhanced by placing red-white bollards, painting kerbs white, by enhancing clearness of the road's shoulder, or by applying high contrast road markings on the side of the cycle path/road.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Unfallverhütung; Fahrbahnmarkierung; Markierung; Radverkehrsanlage; Sichtbarkeit